2022
DOI: 10.3390/su14031112
|View full text |Cite
|
Sign up to set email alerts
|

Economic Anxiety and the Performance of SMEs during COVID-19: A Cross-National Study in Kuwait

Abstract: The focal aim of the project was to assess the economic anxiety (EA) and the performance of small and medium enterprises (SMEs) during partial and full lockdowns in Kuwait. The challenges facing the SMEs during COVID-19 and the potential solutions were also explored. The call for this vital investigation was due to the global economic fallout and the shocking drop within the marketplace caused by the COVID-19 pandemic. A descriptive approach was used for online survey design to collect datasets from 147 SMEs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…More than 10 million people were completely cut off from a large metropolitan area. China's first-level public health emergency reaction was initiated sharply after the lockdown of Wuhan in an attempt at virus containment and prevention (Zainal et al 2022a). Chinese authorities mobilized the entire country to implement the most rigorous and comprehensive control methods possible to save lives.…”
Section: Covid-19 Factors and Sustainable Business Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 million people were completely cut off from a large metropolitan area. China's first-level public health emergency reaction was initiated sharply after the lockdown of Wuhan in an attempt at virus containment and prevention (Zainal et al 2022a). Chinese authorities mobilized the entire country to implement the most rigorous and comprehensive control methods possible to save lives.…”
Section: Covid-19 Factors and Sustainable Business Practicesmentioning
confidence: 99%
“…According to Jesemann et al (2021), one of the steps that must be taken to comprehend the phenomenon of corporate ownership of SD is to investigate the company's attributes. Corporations are required to address the potentially bad impacts their organizational circumstances may have in order to prevent a similar situation from occurring in the future (Zainal et al 2022b). As a result, organizational circumstances influence how businesses respond to SD concerns.…”
Section: Organizational Factors and Sustainable Business Practicesmentioning
confidence: 99%
“…Over the past decade, the world's leading governments, international financial institutions, and the players in the banking system have sought to address the economic (financial, banking, and accounting) problems of the 2007/2008 crisis, accompanied by strong monetary policy expansion and, after some consolidation, the coronavirus crisis posed new challenges to the world economy, including national economies and businesses alike. Several authors found that the COVID-19 impact was evident in all countries, but not with the same strength (Juergensen et al 2020;Nieto and Rubio 2022;Ugurlu and Jindřichovská 2022;Zainal et al 2022). We witnessed strong government intervention in all parts of the world.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, large-scale shutdown has delayed the delivery of upstream production companies. Compared to large enterprises, SMEs have shorter life, lack preparedness when dealing with unforeseen circumstances ( 37 ), lack sufficient cash flow and are more vulnerable to labor shortage, and are affected negatively by the COVID-19 ( 38 ), which will lead to FPD .…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…As an organism with self-healing function, firms will try to fit in with the changes by innovation when it is impacted by crisis. Existing research shows that SMEs will take measures to deal with the COVID-19, for example, transferring to the virtual space to make employees continue working remotely ( 38 ), implementing organization structure innovation ( 4 ), and other MI measures. MI is a new process in which firms bring about a shift in organization strategies, structures, procedures and systems by applying new knowledge and management methods ( 39 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%